Gender and Health : Barriers and Opportunities for Women's Participation in the Private Health Sector in Africa - Monnet, Marguerite (World Bank, Washington, DC, 2015)
Despite their strong contribution to the overall world economic growth, gender gaps are wide in many countries in sub Saharan Africa and low representation of women in the private health sector is wider than in other sectors. While women and youth use the majority of health services both private and public, women are underrepresented as private health care providers and have limited access to financing to open their own private practices. This landscape has prompted the HNP Global Practice to take a critical look at the factors which hamper the growth of female and young private health practitioners vis a vis their male counterparts (usually older and more experienced in their profession). This assessment provides information on ways to close the gap which exists between male private service providers and female providers as well as recommends ways in which the existing gaps can be addressed. The assessment also provides the basis for further developing a strong public- private dialogue in health while providing avenues for building capacities for women to fully contribute to the development of the private health sector through the development of training module to be administered in private training schools as a pilot in Burkina Faso and Mali.